Mercado escolar y oportunidad educacional : libertad, diversidad y desigualdad. - Corvalán, Javier (Ediciones UC, 2016)
School market and educational opportunity: freedom, diversity and inequality, examines the intimate behavior of the Chilean educational system, tensioned between incentives and values, between clients and citizens. This book presents a careful analysis of the consequences of the cultural transformation, which began almost four decades ago, which led to the historic distance between schools and markets narrowing almost completely in Chile. The relevance of this transformation is observed in the role that education has taken in current political, academic and citizen debates.